1979
DOI: 10.1002/aic.690250318
|View full text |Cite
|
Sign up to set email alerts
|

Mixing with helical ribbon agitators: Part III. Non‐Newtonian fluids

Abstract: The use of helical ribbon agitators to mix viscous non-Newtonian fluids has been investigated. A generalized model, based on an appropriate definition of effective viscosity, is proposed to predict power consumption. This model is most successful with fluids that do not have a high degree of elasticity.It was found that the efficiency of mixing of pseudoplastic fluids was about half of that of Newtonian fluids in the same mixer, while the efficiency of mixing viscoelastic fluids was still lower and approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Also included in the same table are the calculated value of Kp using the semi-analytical methods due to Chavan and Ulbrecht (1973), Yap et al (1979) and the empirical correlation proposed by Shamlou and Edwards (1985). While the agreement between the predicted and experimental values of Kp is seen to be moderately good for the models proposed by Chavan and Ulbrecht (1973) and by Yap et al (1979), the correspondence with the results of Shamlou and Edwards (1985) is rather poor. Further examination of this table shows that the value of Kp increases with the decreasing agitator pitch and with the increasing blade width, albeit the latter is a rather small effect.…”
Section: Newtonian Liquidsmentioning
confidence: 95%
See 3 more Smart Citations
“…Also included in the same table are the calculated value of Kp using the semi-analytical methods due to Chavan and Ulbrecht (1973), Yap et al (1979) and the empirical correlation proposed by Shamlou and Edwards (1985). While the agreement between the predicted and experimental values of Kp is seen to be moderately good for the models proposed by Chavan and Ulbrecht (1973) and by Yap et al (1979), the correspondence with the results of Shamlou and Edwards (1985) is rather poor. Further examination of this table shows that the value of Kp increases with the decreasing agitator pitch and with the increasing blade width, albeit the latter is a rather small effect.…”
Section: Newtonian Liquidsmentioning
confidence: 95%
“…This difficulty was circumvented by Metzner and Otto (1957) who introduced the concept of the effective shear rate, that is, where k, is an experimentally determined constant and it is a function of geometry (see, for example, Takahashi et al, 1984). Though originally postulated to be independent of the liquid rheology, recent work, however, suggests that for shear thinning fluids its value also depends upon the power law index (Beckner and Smith, 1966;Yap et al, 1979;Brito et al, 1991). While Eq.…”
Section: Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all close clearance impellers, the helical ribbon impeller, due to its high mixing efficiency [3] and its unique feature of producing axial flow in a stirred tank [4], is widely chosen in mixing highly viscous Newtonian fluids and non-Newtonian fluids. In industrial applications, power consumption is one of the most important factors concerning designers [5][6][7][8]. For Newtonian fluids, theoretical and experimental studies [9,10] have shown that the power number N p is inversely proportional to the Reynolds number Re in the laminar flow:…”
Section: Introductionmentioning
confidence: 99%